Improvement Of Electric Motor Inspection Process In Service Repair Workshop: With Lean Consumption Map Approach - Irani Harefa; Edi Hamdi; Tantri Yanuar; Rina Annindita (Publikasi Indonesia, 2023)
The inspection process at the workshop service repair in this study is a crucial step in terms of providing speedy service to customers. The amount of waste and non-value-added activities in the inspection process is the main problem that must be corrected to increase competitive advantage. This study aims to determine the application of Lean Services in the inspection repair process at workshops service repair using the DMAIC (Define, Measure, Analyze, Improve, and Control) method and the LCM (Lean Consumption Map) tool. This study uses qualitative research methods based on direct observation of work processes and areas, interviews with several competent informants (internal and external), and analysis of forms and procedures documents. From the results of the search, it was found that research on the application of Lean Services is still limited to a few public service sectors, while similar research in the workshops service repair business is still rare and/or in its early stages. The results of this study found that the Lean Services concept with the DMAIC method and LCM tools can be applied and can improve the inspection process in workshops service repair. Then indirectly provide added value, increase trust, and increase customer satisfaction, which can be applied to other similar service workshop businesses. One of the biggest challenges in implementing Lean Services in the workshops service repair business is the non-systematic characteristics of the workshop business, the different types of work, and the varying characteristics of customer satisfaction. This research tries to contribute to and expand the evidence on the application of Lean Services to improve business repair services and encourage research on other similar businesses in the future.